SPE EUROPEC/EAGE Annual Conference and Exhibition 2011
DOI: 10.2118/143292-ms
|View full text |Cite
|
Sign up to set email alerts
|

Partially Separated Meta-Models with Evolution Strategies for Well Placement Optimization

Abstract: Finding the optimal location of non-conventional wells increases significantly the project's Net Present Value (NPV). This problem is nowadays one of the most challenging problems in oil and gas fields development. When dealing with complex reservoir geology and high reservoir heterogeneities, stochastic optimization methods are the most suitable approaches for optimal well placement. However, these methods require in general a considerable computational effort (in terms of number of reservoir simulations, whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 18 publications
0
11
0
1
Order By: Relevance
“…In the following we will also assume not only that the function is partially separable but also that one has access to the function value of each element function. As argued above this assumption is reasonable as it models the case for the well placement problem [4]. History matching is another problem in petroleum engineering in which this assumption is reasonable.…”
Section: Partial Separability and Prob-lem Modelingmentioning
confidence: 94%
See 1 more Smart Citation
“…In the following we will also assume not only that the function is partially separable but also that one has access to the function value of each element function. As argued above this assumption is reasonable as it models the case for the well placement problem [4]. History matching is another problem in petroleum engineering in which this assumption is reasonable.…”
Section: Partial Separability and Prob-lem Modelingmentioning
confidence: 94%
“…A suitable way to model the objective function is to suppose that the profit corresponding to a given well depends only on its location and on the distances of this well to the others. Using the distances between the wells as an element variable implies using a nonlinear combination of the parameters of the problem [4].…”
Section: Partial Separability and Prob-lem Modelingmentioning
confidence: 99%
“…We believe, however, that performance over CMA-ES could be more significantly improved by exploiting, within the algorithm, knowledge, and relevant information about the optimization problem at hand, such as the problem structure. Some first steps in that direction have been conduced in [10,11] where the fact that the objective function can be split into local components referring to each of the wells where each depends on a smaller number of parameters (i.e., partial separability of the objective function) is exploited. Another approach could be to exploit some a priori information such as well allocation factors and connectivity using the work developed in [15].…”
Section: Discussionmentioning
confidence: 99%
“…The method applied by Emerick et al [98] does not utilize a proxy model and in some cases involves more than 100 decision variables and thousands of reservoir simulation runs, possibly limiting the utility of the method. Bouzarkouna et al [99] propose optimal well location can be found through the use of a covariance matrix adaptation evolution strategy that uses adaptive penalization with rejection to deal with constraints. This method is used in conjunction with a meta-model that utilizes an approximate stochastic ranking procedure to rank the fitness of individual wells.…”
Section: Well Placement Optimizationmentioning
confidence: 99%